The determinants of financial planning among youths in Sabah - Abekan, Abqaree Fawwaz; Lajuni, Nelson; Wellfren, Avnner Chardles; Marimo, Edith Clerisa; Mahfirah , Titis Fatarina (Ifma Publishing, 2024)
This study explores the relationship between digital financial literacy and financial attitude to financial planning, with the target population being the youths residing in Malaysia. Questionnaires adopted from past literature were distributed to gather relevant data from the target population, and 300 respondents participated in this study. The results show that digital financial literacy and attitude positively relate to financial planning. Meanwhile, digital financial literacy did not moderate the relationship between financial attitude and financial planning. This study's limitations include omitting other variables, such as behavioural and socio-demographic factors, that may affect financial planning and need to be considered to present a more comprehensive research framework and provide more accurate findings. Lastly, this research guides the relevant authorities in reviewing the country's sufficiency and effectiveness of financial education.